Ḥabs as Common Living Heritage: Beyond the Cash Waqf as Deep Financial Innovation - Abderrazak Belabes (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2025)
Abstract: This conceptual exploration examines the deep meaning of ḥabs as a common living heritage extending beyond mainstream financial interpretations that consider private waqf an innovation of Islam and cash waqf being the best innovation in private waqf. Through the conceptual-hermeneutic approach, Rizq (divine provision) precedes human notions of ownership and city organisation, with the first ḥabs being Bayt (House of Allah) built by Ādam. This research highlights the spiritual relevance of the sacred milieu of Makkah and critiques modern economic concepts that prioritise material growth and individual ownership over the holistic understanding of life and divine provision inherent to the deep meaning of ḥabs. Finally, this research advocates for a re-evaluation of how we perceive wealth, ownership and societal well-being considering ḥabs as a dynamic, connected living system.